Diversity and distribution patterns of Ecuador’s dung beetles (Coleoptera: Scarabaeinae) - Villamarin-Cortez, Santiago; Hankin, Lacey; Coronado, Stephanie; Macdonald, Jacob; Noriega, Jorge Ari (Frontiers in Ecology and Evolution, 2022)
Introduction Ecuador harbors an astounding number of ecosystems and species. However, anthropogenic land-use changes are the primary drivers of biodiversity loss in major taxonomic groups, especially insects. Among them, the Scarabaeinae subfamily containing dung beetles, is an excellent taxon for studying taxonomic and functional diversity, as they are relatively stable taxonomically and have a wide variety of ecological services. Their distribution is mainly influenced by biogeography and climate as their main ecological and environmental factors will allow us to quantify what aspects of diversity are being impacted under different circumstances and at different scales. Methods To understand the main of dung beetle distribution drivers, we analyzed a museum database from the National Institute of Biodiversity, Ecuador (INABIO) of over 5000 dung beetle specimens with 122 species collected throughout the country, we addressed the following questions: i) How does tribe distribution vary across climatic and elevational gradients? and ii) How does functional and taxonomic beta diversity vary across spatial scales? To address them, we focused on three main tribes: Canthonini, Coprini, and Phanaeini. We constructed GLM’s and niche-based models to estimate Ecuador’s distributions based on climate variables to explore potential predictor variables, using tree classification models, along with taxonomic and functional beta diversity across scales. Results The main variables influencing dung beetle distribution were elevation, and precipitation. The Phanaeini niche model is significantly better at predicting dung beetle presence throughout Ecuador than Canthonini and Coprini. We found high turnover in functional groups at larger scales, suggesting that dung beetles show high levels of habitat specialization, which associates to our findings where taxonomic beta diversity was higher in the Amazon basin compared to the coastal region. This may be due to the higher rate of dung production in Amazonia. Our findings also suggest that dung beetles are not found in areas above 2000m, mainly because dung beetles are well adapted to warmer and moist climatic regions. Precipitation and elevation are consistently essential variables for predicting Canthonini and Coprini presence, while temperature explains Phanaeini presence. Low levels of species turnover at the regional scale may be because the total species richness in Ecuador is different, where divergence in taxonomic beta diversity between the two regions is an artifact of such differences in richness in Amazonia versus the coast, the distinction is also due to nonrandomly low taxonomic beta diversity levels in the coastal region. Conclusions Our results provide an essential framework for evaluating potential dung beetle habitat and diversity at different scales; therefore, by identifying dung beetles’ diversity, combined with considerations of habitat fragmentation, human land-use alteration, and climate change, will be an important next step to inform better and prioritize dung beetle conservation efforts in other countries.